Diagnostic accuracy of perfusion-weighted phase-resolved functional lung magnetic resonance imaging in patients with chronic pulmonary embolism - Duan, Jianghui; Xie, Sheng; Sun, Hongliang; An, Jing; Li, Huan; Li, Ling; Grimm, Robert; Voskrebenzev, Andreas; Vogel-Claussen, Jens (Frontiers in Medicine, 2023)
Purpose This study aimed to evaluate the diagnostic performance of perfusion-weighted phase-resolved functional lung (PW-PREFUL) magnetic resonance imaging (MRI) in patients with chronic pulmonary embolism (CPE). Materials and methods This study included 86 patients with suspected chronic thromboembolic pulmonary hypertension (CTEPH), who underwent PREFUL MRI and ventilation/perfusion (V/Q) single-photon emission computed tomography/computed tomography (SPECT/CT). PREFUL MRI was performed at 1.5 T using a balanced steady-state free precession sequence during free breathing. Color-coded PW images and quantitative parameters were obtained by postprocessing. Meanwhile, V/Q SPECT/CT imaging was performed as a reference standard. Hypoperfused areas in the lungs were scored for each lobe and segment using V/Q SPECT/CT images and PW-PREFUL MR images, respectively. Normalized perfusion (QN) and perfusion defect percentage (QDP) were calculated for all slices. For intra- and interobserver variability, the MRI images were analyzed 2 months after the first analysis by the same radiologist and another radiologist (11 years of lung MRI experience) blinded to the results of the first reader. Results Of the 86 enrolled patients, 77 met the inclusion criteria (36 diagnosed with CPE using V/Q SPECT/CT and 41 diagnosed with non-CPE etiology). For the PW-PREFUL MRI, the sensitivity, specificity, accuracy, and positive and negative predictive values for the diagnosis of CPE were 97, 95, 96, 95, and 98% at the patient level; 91, 94, 93, 91, and 94% at the lobe level, and 85, 94, 92, 88, and 94% at the segment level, respectively. The detection of segmental and subsegmental hypoperfusion using PW-PREFUL MRI revealed a moderate agreement with V/Q SPECT/CT (κ = 0.65; 95% confidence interval: 0.61–0.68). The quantitative results indicated that the QN was lower in the CPE group than in the non-CPE group [median score (interquartile range, IQR) 6.3 (2.8–9.2) vs. 13.0 (8.8–16.7), p < 0.001], and the QDP was higher [median score (IQR) 33.8 (15.7–51.7) vs. 2.2 (1.4–2.9), p < 0.001]. Conclusion PREFUL MRI could be an alternative test to detect CPE without requiring breath-hold, contrast agents, or ionizing radiation.